The ethylene response factor Pti5 contributes to potato aphid resistance in tomato independent of ethylene signalling - Wu, Chengjun (J Exp Bot, 2015)
Ethylene response factors (ERFs) comprise a large family of transcription factors that regulate numerous biological processes including growth, development, and response to environmental stresses. Here, we report that Pti5, an ERF in tomato [Solanum lycopersicum (Linnaeus)] was transcriptionally upregulated in response to the potato aphid Macrosiphum euphorbiae (Thomas), and contributed to plant defences that limited the population growth of this phloem-feeding insect. Virus-induced gene silencing of Pti5 enhanced aphid population growth on tomato, both on an aphid-susceptible cultivar and on a near-isogenic genotype that carried the Mi-1.2 resistance (R) gene. These results indicate that Pti5 contributes to basal resistance in susceptible plants and also can synergize with other R gene-mediated defences to limit aphid survival and reproduction. Although Pti5 contains the ERF motif, induction of this gene by aphids was independent of ethylene, since the ACC deaminase (ACD) transgene, which inhibits ethylene synthesis, did not diminish the responsiveness of Pti5 to aphid infestation. Furthermore, experiments with inhibitors of ethylene synthesis revealed that Pti5 and ethylene have distinctly different roles in plant responses to aphids. Whereas Pti5 contributed to antibiotic plant defences that limited aphid survival and reproduction on both resistant (Mi-1.2+) and susceptible (Mi-1.2–) genotypes, ethylene signalling promoted aphid infestation on susceptible plants but contributed to antixenotic defences that deterred the early stages of aphid host selection on resistant plants. These findings suggest that the antixenotic defences that inhibit aphid settling and the antibiotic defences that depress fecundity and promote mortality are regulated through different signalling pathways.